Conversation Analysis: Communication Across Cultures - Lale Fatma Yulia Ningsih (JURNAL AVESINA, 2019)
The study of intercultural communication continues to grow in importance in response to greater population mobility, migration and globalization. Communication across culture explores how cultural context affects the use and interpretation of language. It provides accessible and interdisciplinary introduction to language and language variations in intercultural communication. This is done by drawing on both classic and cutting-edge research from pragmatics, discourse analysis, sociolinguistics, anthropology and politeness study. This study aims to discuss the variety of linguistic and non-linguistic features generated by participants in social interaction. The first part will examine turn-taking dynamic in a conversation between three students who have different cultural backgrounds. Later, the last four sections of the study also take into account power relation among the participant, the collaboration, politeness strategy employed as well as embedded speech act in the conversation.